Employees’ attitude and behavior toward technology in relation to their job performance - Mambo, Lenda (YUME : Journal of Management, 2024)
Office technology enhances employes’ performance, but it also may hinder their job achievement. The study is aimed to find out the relationship between employees’ attitudes and behaviors toward office technology and how it affects to their work performance. Using descriptive statistics, the study found that employees with excellent job performance and good job performance are the one who embrace office technology. They believe that mastering office technology enhances their work performance, the same result also with mediocre performance employes who also considers office technology improved their work achievement, but low-performing employees with low job performance achievement perceive office technology programs as burdens, an activity that annoys them and they won’t enjoy and be happy with it. A multiple regression result showed that both attitude and behavior are significant predictors of job performance (JP) with regression coefficients p-values 0.0132 less than 0.05 and the coefficient for attitude is 0.175, and the coefficient for behavior is 0.718. However, the multiple R-squared value of 0.274 indicates that only about 27% of the variance in job performance can be explained by the model. Keywords: attitude toward office technology, behavior toward office technology, job performance achievement